أثر الوسائط الرقمية على وظيفة العلاقات العامة بالمؤسسات الخدماتية صفحة الفايسبوك بمديرية التوزيع لمؤسسة سونلغاز بالمسيلة نموذجا - خولة, سعداوي (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2022)
تعد مؤسسة سونلغاز من بين أهم المؤسسات الخدماتية التي تنشط بها إدارة العلاقات العامة، وذلك انطلاقا من تعامل هذه الأخيرة مع مختلف الجماهير، وعليه تهدف هذه الدراسة التي أجريت بمؤسسة مديرية التوزيع سونلغاز –ولاية المسيلة- والتي تحمل عنوان أثر الوسائط الرقمية على وظيفة العلاقات العامة بالمؤسسات الخدماتية، صفحة الفيسبوك..الخ. - معرفة مدى استفادة قسم العلاقات العامة في المؤسسة الخدماتية في زيادة استخدام التطور الكبير للتكنولوجيا الرقمية. - الكشف عن أهم الوسائط الرقمية التي تستخدمها العلاقات العامة للتواصل مع جمهورها. - تسليط الضوء على الخدمات التي تقدمها مؤسسة سونلغاز- المسيلة- لزبائنها عبر العلاقات العامة الإلكترونية. - محاولة معرفة آراء الجمهور حول أداء العلاقات العامة الإلكترونية في المؤسسة. - الاستفادة من نتائج هذه الدراسة ووضع الاقتراحات. وقد اعتمدت في دراستي على المنهج المسحي في المسح بالعينة، لأنه يناسب هذا النوع من البحوث، أما عن عينة الدراسة فقد اخترت العينة القصدية، وهذا للإجابة على التساؤل الرئيسي لهذه الدراسة: - كيف تمارس مؤسسة سونلغاز العلاقات العامة عبر الصفحة الرسمية على الفيس بوك؟. ويندرج تحته أسئلة فرعية هي: - ما رأي موظفي مؤسسة سونلغاز في انعكاسات التكنولوجيا الحديثة على أداء العلاقات العامة؟. - ماهي أهم الوسائط الرقمية التي تستخدمها مؤسسة سونلغاز لتفعيل أداء العلاقات العامة؟. وبعد الدراسة الميدانية وجمع تحليل البيانات تبين أن: - تنوع مضامين المواقع الإلكترونية، وهذا التنوع يخدم هدفاً واحدا هو التعريف بالمؤسسة وأنشطتها. - تعمل العلاقات العامة الإلكترونية على استقطاب الجماهير الخارجية باستخدام مميزات الفايسبوك. اهتمام مسؤولي العلاقات العامة بتغذية مختلف المواقع الإلكترونية بجديد الخدمات والعروض لمؤسسة سونلغاز. - تسعى مؤسسة سونلغاز لخلق علاقة ولاء إلكترونية جمهورها، وذلك من خلال إتاحة الفرصة لهم لإبداء آرائهم وتعليقاتهم حول نشاطات المؤسسة. - تحديث صفحة الفايسبوك لا يتم بصورة منتظمة حيث يتم تحديث الصفحة فقط في حال وجود خبر أو نشاط جديد للمؤسسة وهذا يقلل من اهتمام الجمهور بهذه الصفحة. - تقوم مؤسسة سونلغاز بوضع جدول نشاطاتها والمناسبات التي ترعاها على صفحة الفايسبوك للمؤسسة فقط. The Sonelgaz Foundation is among the most important service institutions in which the Public Relations Department is active, based on the latter’s interaction with various audiences. Accordingly, this study, which was conducted at the Sonelgaz Directorate of Distribution Foundation - M’sila State - aims to bear the title of the impact of digital media on the function of public relations in institutions. Services, Facebook page..etc. - Knowing the extent to which the public relations department in the service organization has benefited in increasing the use of the great development of digital technology. - Disclose the most important digital media used by public relations to communicate with its audience. - Shedding light on the services provided by the Sonelgaz Foundation - Al-Masila - to its customers through electronic public relations. - Attempting to know the public's opinions about the performance of electronic public relations in the institution. Benefiting from the results of this study and making suggestions. In my study, I relied on the survey method in the sample survey, because it suits this type of research. As for the study sample, I chose the intentional sample, and this is to answer the main question of this study: - How does the Sonelgaz Foundation practice public relations through the official Facebook page? It includes sub-questions: - What is the opinion of Sonelgaz employees about the implications of modern technology on the performance of public relations? What are the most important digital media used by Sonelgaz to activate the performance of public relations? After the field study and data analysis, it was found that: - Diversity of the contents of websites, and this diversity serves one goal, which is to introduce the institution and its activities. - Electronic public relations work to attract external audiences using the features of Facebook. The interest of public relations officials in feeding the various websites of the new services and offers of the Sonelgaz Corporation. - The Sonelgaz Foundation seeks to create an electronic loyalty relationship for its audience, by giving them the opportunity to express their opinions and comments about the Foundation's activities. The Facebook page is not updated regularly, as the page is updated only in the event of a new news or activity for the institution, and this reduces the public's interest in this page. - The Sonelgaz Foundation puts its schedule of activities and sponsored events on the Foundation's Facebook page only.
Keywords: أثر الوسائط الرقمية–العلاقات العامة–العلاقات العامة الإلكترونية–مؤسسة سونلغاز–وسائل التواصل الاجتماعي - الفيسبوك.